The Influence of Health Education on Feeding Rules and Eating Behavior in Toddlers (HEALTH CARE: JURNAL KESEHATAN, 2024)
Background: Misunderstanding among parents leads to malnutrition in children. Eating problems in toddlers include picky eaters, selective eaters, and small eaters. Failure in feeding practices affects the growth and development of toddlers. Research Objective: To examine the effect of health education on feeding rules and eating behavior in toddlers. Method: This study is a quantitative research with a pre-experimental design using a one-group pre-test and post-test approach. The research was conducted in the working area of Tenayan Health Center, Pekanbaru City, from April to July 2024. The population consisted of all mothers with toddlers in the working area of the Tenayan Health Center, with a sample size of 31 respondents. Data analysis was performed using the Wilcoxon Ranks Test. Results: The study found that health education significantly affected feeding rules (p-value = 0.000) and eating behavior (p-value = 0.000) in toddlers in the working area of the Tenayan Health Center, Pekanbaru City, with p-value < 0.05. Conclusion: Health education using diverse methods by healthcare professionals on an ongoing basis is necessary to change eating behavior and feeding rules among parents with toddlers to prevent malnutrition in children.